HVAD GØR LYD TIL STØJ? - Lund, Søren Peter; Burr, Hermann; Nielsen, Per Møberg; Kristiansen, Jesper (Tidsskriftet Antropologi, 2006)
Sounds are found everywhere, including the working environment. When sounds are unwanted and annoying they are perceived as noise. An increasing number of people in Denmark are reporting that they are exposed to loud noise in their working environment. It is noteworthy that the reported incidence of noise exposure comes from non-industrial trades, for example, from day-care institutions, and from schoolrooms. In order to reduce annoyance due to work-related noise exposure, it is necessary to identify the circumstances and factors that are important when sound is perceived as noise. The results of our research demonstrate that noise of even low sound levels can cause considerable annoyance. Moreover, a number of other factors are important in making sounds being perceived as noise. They are, among others, the information content of the sounds, the predictability and the possibility to control the sound, the characteristics of the work tasks, prevention of the noise, and various individual factors, such as noise sensitivity and hearing. Finally, not only is annoyance the effect of exposure to noise in the working environment; our research points to the conclusion that sustained exposure to noise can result in stress.